PENGARUH MUTU LAYANAN SARANA DAN PRASARANA TERHADAP KEPUASAN SISWA - Sairi, Asril; Safrizal, M. (Graduate Program Magister Manajemen Pendidikan, 2018)
Generally, this study aims to find out the true picture regarding the quality of infrastructure services to the satisfaction of students in SMA Muhammadiyah 1 Palembang. The method used in this research is descriptive method with quantitative approach. The technique of collecting data using questionnaires that were distributed to 275 students as the study sample. The result of the calculation using the general trend show that student satisfaction in the high category with an average score of 4.24 and quality of services in environmental infrastructure SMA Muhammadiyah 1 Palembang included in the high category with an average score of 3.53. The correlation analysis using Pearson Product Moment, the correlation coefficient between variables X and Y is equal to 0.786 which shows that the correlation between the two variables are at high-level relations. The results of the significance test that is 5.264 > 1,968692, it means that the correlation coefficient between variables X and Y are significant with linear regression analysis equation Å¶ = 50,022 + 0,493X1, this means that any change in one unit variable X will be followed by a change of variable Y for 0,493. It is concluded that there is a positive and significant relationship of quality service infrastructures on studentsâ satisfaction in SMA Muhammadiyah 1 Palembang.